IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS VII SMP NEGERI 2 BATANG - Ain Nur Safira; Ani Rakhmawati; Muhammad Aditya Wisnu Wardana (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
The Ministry of Education and Culture develops the Independent Curriculum (Which previously called as curriculum prototype) as a learning recovery effort in the midst of conditions that are expected to improve. Learning recovery is carried out to overcome the learning loss experienced by students during the pandemic. The purpose of this study was to find out whether the independent curriculum had been properly implemented at SMP Negeri 2 Batang. This study uses qualitative methods and research techniques in the form of interviews with teachers women lesson language Indonesia Of Junior High School Negeri 2 Batang as well as field studies or field research. Project strengthening profile student Pancasila has been implemented with the theme of Local Wisdom in the form of exploring herbal ingredients, all things in the Tiban market, traces of ancestral lands, and old school culinary delights. So, from this study it can be concluded that SMP Negeri 2 Batang has implemented independent curriculum-based learning and has developed and implemented projects to strengthen the profile of Pancasila students in accordance with the recommendations of the Ministry of Education and Culture